PENGARUH LATIHAN FINDER KEEPERS TERHADAP KECEPATAN PADA SISWA YANG MENGIKUTI EKSTRAKULIKULER NOMOR LOMPAT JAUH DI SMK PGRI PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the results of the interview with the sports teacher, Mr. Mardoni Putra, it turned out that the students' long jump ability was still not maximal. This is due to the lack of walking speed when making the jump. Based on the results of the interview, the weakness that comes up in students is that they occur when making a jump, where the speed is not good. Continuous exercises are needed to get the maximum long jump result. Many drills can increase speed, including Finder keepers. The aim of this study was to determine the effect of Finder Keepers training on speed towards students who participate in long jump extracurricular at SMK PGRI Pekanbaru. The population in this study consisted of students who made the extracurricular long jump as many as 10 sons. The sample used is 10 people by research using the total sampling technique. The instrument in this research was a walking speed of 30 meters. The results obtained were analyzed using the t-test. Based on the results of this research, a t-test was performed that resulted in a t-count of 9.028 with a t-table of 1.796 so that H_a was accepted, at the alpha (α) 0.05 level. It can be concluded that there is an the effect of Finder Keepers training on speed towards students who participate in long jump extracurricular at SMK PGRI Pekanbaru.Key Words: Speed, long jump